Diffraction of a cylindrical acoustic pulse by a wedge - BRAŃSKI, Adam; ŻYSZKOWSKI, Zbigniew (Archives of Acoustics, 1985)
In the paper, the diffracted field of a cylindrical pulse, approximating an explosion, at a wedge with the V angle α = 3/2 π, was calculated. This problem was solved on the basis of the Oberhettinger theory. The drop of the acoustic pressure level at the edge of the wedge, depending on the energy of the source, and the drop of the pressure level along the wall of the wedge in the silence zone, were calculated.